Electrophoretic deposition (EPD) of Na-montmorillonite nanoclay from clay mineral slurries - Bernardo, Ivyleen C.; Diaz, Leslie Joy L. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Electophoretic deposition (EPD) is a coating technique where powders from the slurry are deposited on the substrate. In this study, EPD was explored and investigated as a selective deposition technique to separate Na-Montmorillonite (Na-MMT) nanoclay from Kaolinite in an aqueous slurry of synthetic combination of Na-MMT and kaolinite. The success of the study is based on the recovery of specific clay minerals and accessory minerals from clay slurries by EPD using stainless steel electrodes. Effects of applied potential (E) and electrode gaps (G) on the yield, on the Na-MMT - Kaolinite ratio, and on the Na-MMT recovery of the EPD deposits were investigated. ANOVA of two-factor fixed effect Model was employed with F-test at 5% significance level. Determination of clay components of dried EPD deposits was done by XRD. The main effects and the interaction of applied potential and electrode gap on the responses were found significant. The 4V-1 centimeter gap obtained highest yield of deposits and highest recovery of Na-MMT from synthetic EPD deposits while 4V-2 centimeter gap obtained the highest ratio of Na-MMT-Kaolinite at an average of 5.2:1 of 2:1. This shows EPD can separate and recover Na-MMT nanoclay from aqueous slurry containing combination of clay minerals at specific applied-electrode gap combination.
Thesis (Doctor of Philosophy in Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Electrophoretic deposition; Coatings